2007
DOI: 10.1158/0008-5472.can-06-3867
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor Activity of the Lysyl Oxidase Propeptide Reverses the Invasive Phenotype of Her-2/neu–Driven Breast Cancer

Abstract: Expression of the lysyl oxidase gene (LOX) was found to inhibit the transforming activity of the ras oncogene in NIH 3T3 fibroblasts and was hence named the ras recision gene (rrg). Lysyl oxidase (LOX) is synthesized and secreted as a 50-kDa inactive proenzyme (Pro-LOX), which is processed by proteolytic cleavage to a functional 32-kDa enzyme and an 18-kDa propeptide (LOX-PP). Recently, the ras recision activity of the LOX gene in NIH 3T3 cells was mapped to its propeptide region. Here, we show for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 47 publications
9
134
1
2
Order By: Relevance
“…Many studies have shown that increased LOX expression is associated with malignant progression of cancer cells [17,31,50], whereas some studies reported that 50-kDa pro-LOX or its cleaved 18-kDa product (LOX-PP) may have tumor-suppressive function [21][22][23][24]. One of the reasons responsible for the differences between these reports and our study might be the different the cell lines.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Many studies have shown that increased LOX expression is associated with malignant progression of cancer cells [17,31,50], whereas some studies reported that 50-kDa pro-LOX or its cleaved 18-kDa product (LOX-PP) may have tumor-suppressive function [21][22][23][24]. One of the reasons responsible for the differences between these reports and our study might be the different the cell lines.…”
Section: Discussioncontrasting
confidence: 78%
“…Involvement of the LOX family is widely accepted as a poor prognostic factor for patients with cancer [15][16][17][18][19][20]. By contrast, Kaneda et al [21] reported that LOX is a tumor suppressor gene inactivated by heavy methylation of the 5 0 untranslated region and loss of heterozygosity in gastric cancers, and several studies have reported that LOX-PP has tumor suppressor activity [22][23][24]. Both downregulation and upregulation of LOX in tumor tissues and cancer cell lines have been described [25][26][27][28], suggesting a paradoxical role for LOX as a tumor suppressor [21,29] as well as a metastasis promoter gene [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…LOX is also a tumor suppressor and it inhibits ras-dependent transformation of fibroblasts [4,8,14]. The tumor suppressor activity of LOX has been mapped to the pro-peptide region [24] and LOX-PP inhibits tumor formation by breast cancer cells in mice [19]. In normal osteoblasts, LOX-PP accumulates in cultures [9] and recombinant LOX-PP is taken up by cells and accumulates over time associated with microtubules [7].…”
Section: Discussionmentioning
confidence: 99%
“…Primary vascular SMCs were grown with LOX-PP (10 μg/ml) or vehicle was then the number of viable cells per culture determined after 48 hours. The concentration of LOX-PP was based on preliminary dose response-and published studies [19,24,28]. Figure 1A shows that LOX-PP significantly inhibits the growth of SMC cultures.…”
Section: Lox-pp Inhibits Smc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation